Latihan Fartlek Time To Distance dan Time To Time: Solusi Optimal untuk Meningkatkan Performa Kecepatan dan Daya Tahan Pelari Jarak Menengah - Julifais Neni Dwi Rusdita; Oce Wiriawan; Bhekti Lestari; Fifit Yeti Wulandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to examine the comparative effectiveness of both models in improving runners’ speed and endurance and to determine which produces superior physiological adaptations. A quasi-experimental design with a two-group pretest–posttest format was used. Twelve male athletes (aged 17–22 years) were divided into two groups: K1 (Time to Distance, n=6) and K2 (Time to Time, n=6). Speed (30 m sprint) and endurance (1600 m run) tests were administered before and after six weeks of training at 75–90% HRmax intensity. Significant improvements were observed in both groups (p < 0.05). For speed, K1 improved from 4.35 ± 0.21 s to 3.95 ± 0.18 s (p = 0.001; d = 1.90), while K2 improved from 4.33 ± 0.24 s to 4.12 ± 0.19 s (p = 0.015; d = 1.05). For endurance, K1 improved from 6.45 ± 0.31 min to 5.98 ± 0.27 min (p = 0.001; d = 2.00), and K2 from 6.48 ± 0.34 min to 6.18 ± 0.29 min (p = 0.012; d = 1.15). Independent t-test results confirmed significant intergroup differences (p < 0.05). The study concludes that the Fartlek Time to Distance model is more effective in enhancing speed and endurance through improved anaerobic adaptation and biomechanical efficiency. Practically, this research provides an evidence-based foundation for coaches and athletes to optimize performance through structured fartlek training design.IM Keywords: Fartlek, speed, endurance, middle-distance runners, athletic performance